Acute onset of Guillain-Barré syndrome after multiple spine surgeries: A rare case report - Khalil Komlakh; Alireza Manafi-Rasi; Ahmadreza Mirbolook; Mojtaba Baroutkoub; Sohrab Salimi; MirBahador Athari (Advanced Biomedical Research, 2022)
Guillain-Barré syndrome is an autoimmune disorder presented by ascending paralysis and areflexia. The condition has been reported after many infections, but Guillain-Barré syndrome after spine surgery is rare. We, herein, present a case of Guillain-Barré syndrome after multiple spine surgeries for degenerative lumbar scoliosis. A 60-year-old woman with degenerative scoliosis underwent surgery for the third time and developed Guillain-Barré syndrome 3 weeks after the final operation. The patient received intravenous immune globulin therapy and needed mechanical ventilation and intensive care. She was discharged in good condition after 5 weeks.